Expression of the ogt gene in wild-type and ada mutants of E. coli. - Potter, P M (1989)
O6-alkylguanine (O6-AlkG) DNA alkyltransferase (ATase) and alkylphosphotriester (AlkP) ATase activity have been quantitated individually in extracts of various E. coli strains by means of ATase specific DNA substrates. O6-AlkG ATase activity was higher than AlkP ATase activity in the wild-type strains F26, AB1157 and SB229 and in the ada- mutants PJ1, PJ3, PJ5 and PJ6 indicating a 5-70 times higher level of expression of the ogt gene than the ada gene. The ada- mutant strains BS23, BS73 and GW5352 expressed O6-AlkG ATase but not AlkP ATase activity indicating expression only of the ogt gene. Southern analysis of DNA from F26, BS23, BS73, PJ1 and GW5352 showed a consistent pattern of hybridisation to an ogt probe but not to an ada probe. Exposure of E. coli to adaptive doses of N-methyl-N-nitro-N-nitroso-guanidine (MeNNG) caused an increase in AlkP ATase activity in F26, AB1156, SB229, PJ1, PJ3, PJ5 and PJ6. O6-AlkG ATase activity also increased in F26, AB1157 and SB229 but decreased to almost undetectable levels in all other strains examined except PJ3 where it remained constant. MeNNG increased ada mRNA abundance in F26 but no ada mRNA was detected in BS23, BS73 or GW5352: there was no evidence for increased ogt mRNA in any of the strains examined. In a limited survey, other bacterial strains have been shown to possess an ogt-like ATase activity.